2021
DOI: 10.3390/su132212790
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies, Circular Economy Practices and Environmental Policies in the Era of COVID-19

Abstract: The degradation of the environment is associated with economic activity, particularly with the linear way in which the economy does not make efficient use of resources. However, the circular economy is opposed to this linear paradigm, since it makes the most of the resources in trying to achieve zero waste. In this context, this study investigates the relationship between industry 4.0 technologies, COVID-19 outbreak, environmental regulation policies and circular economy practices. A questionnaire is designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…Khan et al [19] found that fossil fuels reduced and renewable energy improved the environmental quality in Europe. Moreover, bulk literature has suggested that the concept of a circular economy and green business practices would serve to promote eco-environmental performance [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [19] found that fossil fuels reduced and renewable energy improved the environmental quality in Europe. Moreover, bulk literature has suggested that the concept of a circular economy and green business practices would serve to promote eco-environmental performance [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the Athletes' Village built for the sports events can be considered a typical case of circular economy. By operating the Athletes' Village, it is possible to explore and practice the application of circular economy in the community, which will provide technical support for the future large-scale promotion of cleaner and more environmentally friendly production and living systems, thus contributing to sustainable development of the hosts (Khan et al, 2021c). Therefore, this study believes that organizing comprehensive sports events can realize the green and low-carbon development of each city through green technology innovation.…”
Section: Technological Innovation Effectmentioning
confidence: 97%
“…The continuous deterioration in the state of the climate has raised serious concerns about mitigating its harmful effects (Khan et al, 2021c). It has now become imperative to discuss the causes and the possible solutions for curtailing the current levels of environmental contamination, which otherwise may cause irreparable damage to the world's environment, resources, and population.…”
Section: Literature Reviewmentioning
confidence: 99%